EFEK PENDIDIKAN KESEHATAN KOMUNITAS TERHADAP PENGETAHUAN, KETRAMPILAN DAN PENERIMAAN TENTANG PROGRAM DETEKSI DINI KANKER SERVIKS DI DESA REMPOA KECAMATAN BATURADEN KABUPATEN BANYUMAS. - Mekar, Saryono dan (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
Cervix cancer is the common cancer from ten rank of caused dead in cancer women. On the other hand, 70% over case that go to hospital are prolonged stadium. The reseach aim  was to know the effect of community health education to increase knowledge, skill and awareness to early detection of cervical cancer on fertile women in Rempoa village, Baturaden. The research method was pre-experiment. Reseacher giving cervical cancer material with discussion technique and than PAP SMEAR video exercise for early detection of cervical cancer. The program was preceded by pre test and post test in ended session. The test used to evaluate minimal capability and knowledge that reach. Cervical cancer exercise video used to evaluate psikomotor capacity. The processing data used to SPSS program with t test. The result of this research was low score in cervical cancer knowledge (mean = 4,9) before socialization and the mean made 6,5 after socialization. The t test showed that there was a different between before and after cervical cancer socialization significantly (p<0,005). The cervical cancer early detection health education program could increase responden knowledge for early detection. Keywords: community health education, early detection, cervical cancer Kesmasindo: Vol 3(1) 210;1-7